Association of the IL-6R gene polymorphic variant rs2228145(C>A) with IL-6 gene polymorphisms in a healthy cohort of Turkish population - Karcıoğlu Batur, Lutfiye; Savaş, Serdar; Girgin, Erhan; Hekim, Nezih (Genes and immunity, 2022)
The main aim of this study was to investigate the relationship of the carriership of rs2228145 allelic variations of IL-6R with two other allelic variations in IL-6 gene at rs1800795 and rs1800796 loci and with the laboratory data of a healthy cohort of the Turkish population. The data of 121 healthy Turkish subjects (aged 12–84 years) including the past diseases, comorbidities were collected. The laboratory parameters were compared by the frequency of alleles of rs2228145 (C>A). The possible association of polymorphism at rs2228145 locus with the age, gender, and body mass index (BMI) and the frequencies of alleles of rs1800795 and rs1800796 polymorphisms were evaluated. The majority of the subjects had allele A at rs2228145 locus and allele G at rs1800796 locus. The number of white blood cells, platelets, neutrophils and monocytes were significantly higher in the subjects with allele C than those with allele A at rs2228145 locus ( P < 0.05). The concentrations of total and direct bilirubin, iron, Sex Hormone Binding Globulin (SHBG) and folic acid of the subjects with allele C were significantly lower than those with allele A ( P < 0.05). The uric acid and fasting insulin levels were higher in the subjects with allele C compared with those allele A ( P = 0.04). The diversities of the hematological parameters, laboratory findings of liver function tests and renal panel and hormone levels may be explained by the variants of rs2228145 locus at IL-6R gene among healthy Turkish individuals.